Pengaruh Standar Operasional Prosedur dan Pengawasan Terhadap Kinerja Karyawan PT. Karya Teknik Cemerlang Makassar. - M. Fajar Basri Sutte; Muhammad Badar; Normiyati N (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2023)
This study aims to determine the effect of Standard Operating Procedures and Supervision on Employee Performance of the Company Karya Teknik Cemerlang Makassar. This research was conducted at the Cemerlang Engineering Works Company Makassar, this company is engaged in gas cylinder maintenance workshop services in collaboration with the Pertamina Company. This study uses quantitative data analysis as the main technique, specifically using a correlation test tool to test and analyze data using SPSS software version 26. The results of this study indicate that the Standard Operating Procedure (SOP) on employee performance at the Makassar Cemerlang Engineering Works Company has a significant effect, Supervision has a significant effect on employee performance at the Makassar Cemerlang Engineering Works Company and Standard Operating Procedure (SOP) and supervision simultaneously affect employee performance at the Makassar Cemerlang Engineering Works Company.